(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
This study was carried out at the piggery unit of Alex Ekwueme Federal University Ndufu-Alike Ikwo, Abakaliki, Ebonyi State to evaluate the haematological and serum biochemical estimates of weaner pigs fed graded levels of tigernut chaff enzyme based diets. Sundried tigernut chaff (waste from tigernut processing) was collected from reputable tiger nut milk processors at Abakaliki, Ebonyi State, sun-dried for 5-7 days for the determination of proximate composition. Four experimental diets were formulated such that tigernut (Cyperus esculentus) chaff treated with multi-enzyme notably Growin ACT was included at 0%, 5%, 10% and 15% dietary levels coded (T1), (T2), (T3) and (T4) respectively. Data obtained from the study was subjected to the one-way analysis of variance (ANOVA) using general linear model of SPSS version. Results of the study showed that pigs fed enzyme supplemented tigernut chaff based diets showed significant (P<0.05) improvement in haematological parameters notably Hb, RBC, WBC, and PCV, with increasing dietary level of TNC while serum biochemical values such as albumin, serum glutamic oxaloacetic transferase (SGOT), Serum glutamic pyruvic transferase (SGPT) and creatinine reduced, as the dietary levels of TNC increased in the diets. In view of the above results, enzyme-supplemented tigernut chaff should be included in the ration of weaner pigs as a partial replacement for maize at 15% level for optimum haematological and serum biochemical profile, increased productivity and maximum economic benefits so as to make animal protein available at a reduced cost.